Impacts to Teacher-Student Relationships on Students’ Academic Performance at The Secondary School Level in Dhaka City - Mustary, Mashraky (International Journal of Psychosocial Rehabilitation, 2020)
This study seeks to create understanding on the significance between the relationship between teachers and students in an academic set up. The research has used a simple random sampling method to determine a population sample of 200 respondents. This sample size consisted of 100 students and 100 teachers. Data was collected by use of questionnaire forms and interviews. After collecting the primary data, the data was subjected into quantitative analysis using various statistical methods so as to get understanding of the topic which was being investigated. Based on the research, it was realized that there is a positive correlation between teach-student relationship and academic performance. This means that positive relationship between teachers and students improve the performance of students. On the other hand, negative relationship between teachers and students deteriorate the performance of students. It was also realized that learners find it easy to share with teachers the predicaments they undergo when there is a positive relationship. However, in a situation where teachers do not show any concern to students, academic performance usually deteriorates because students are not in close intimacy with the teachers. Therefore, the study recommended that teachers should devise mechanism of developing a positive relationship with students so as to address their needs including those associated with academic performance.